The Effect of Complications on Oncological Outcomes of Colorectal Cancer Patients After Primary Surgery: A Propensity Score Matching Analysis - Liu, Xiao-Yu; Zhang, Bin; Kang, Bing; Cheng, Yu-Xi; Yuan, Chao; Tao, Wei; Wei, Zheng-Qiang; Peng, Dong (Frontiers in Oncology, 2022)
Purpose The purpose of this study is to explore the oncologic outcomes of complications on colorectal cancer (CRC) patients who underwent primary surgery using a propensity score matching (PSM) analysis. Methods A retrospective study was conducted from Jan 2011 to Jan 2020 in a clinical center. The overall survival (OS) and disease-free survival (DFS) were compared among the no complications group, the major complications group and the minor complications group. Results A total of 4250 CRC patients who underwent radical primary surgery were included in the current study. Among them, 927 (21.8%) patients suffered complications. After 1:1 ratio PSM, there were 98 patients in the major complications group and in the minor complications group, and 911 patients in the overall complications group and in the no complications group. There was no significant difference in terms of baseline information after PSM (p>0.05). Complications were independent predictors of OS (p=0.000, HR=1.693, 95% CI=1.476-1.941) and DFS (p=0.000, HR=1.555, 95% CI=1.367-1.768). In terms of specific tumor stage, the no complications group had better OS on all stages (p=0.006) and stage III (p=0.003) CRC than the complications group after PSM. Furthermore, the no complications group had better DFS on all stages (p=0.005) and stage III (p=0.021) CRC than the complications group after PSM. However, there was no significant difference between the minor complications group and the major complications group in different tumor stages (p>0.05). Conclusion Complications were associated with poor prognosis of CRC and surgeons should be cautious of the adverse events.